2019
DOI: 10.1371/journal.pone.0225601
|View full text |Cite
|
Sign up to set email alerts
|

The value of kinetic glomerular filtration rate estimation on medication dosing in acute kidney injury

Abstract: BackgroundIn acute kidney injury (AKI), medication dosing based on Cockcroft-Gault creatinine clearance (CrCl) or Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) estimated glomerular filtration rates (eGFR) are not valid when serum creatinine (SCr) is not in steady state. The aim of this study was to determine the impact of a kinetic estimating equation that incorporates fluctuations in SCrs on drug dosing in critically ill patients.MethodsWe used data from participants enrolled in the NIH Acute Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 34 publications
1
15
0
1
Order By: Relevance
“…One study of elderly people with stable renal function in a long-term care facility found a concordance of only 60% between the 2 methods [9]. Our findings are comparable to a recent study of participants with acute respiratory distress syndrome in which the use of KeGFR was shown to impact drug dosing in a quarter of all subjects, more so in patients with AKI compared to CGeCrCl and CKD-EPI GFR during the first week of admission [10].…”
Section: Discussion/conclusionsupporting
confidence: 72%
“…One study of elderly people with stable renal function in a long-term care facility found a concordance of only 60% between the 2 methods [9]. Our findings are comparable to a recent study of participants with acute respiratory distress syndrome in which the use of KeGFR was shown to impact drug dosing in a quarter of all subjects, more so in patients with AKI compared to CGeCrCl and CKD-EPI GFR during the first week of admission [10].…”
Section: Discussion/conclusionsupporting
confidence: 72%
“…Other options include approaches such as the kGFR equation, which has provided heterogeneous results when applied to drug dosing. [44][45][46] Potential limitations of kGFR include the use of baseline clearance and maximum change in SCr, which are subjective and might not be suitable in a clinical trial setting, and the inability to consider urine data. Again, a model-based approach seems preferable.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 describes the studies evaluating the KeGFR approach in critically ill patients, a population with frequently changing kidney function. 15,21-26 All the studies based the KeGFR calculations on the method of Chen. 10 Based on the results of these investigations, we suggest that standard methods be used when SCr is stable with only minor fluctuation.…”
Section: Studies Evaluating Kinetic Estimates Of Clearancementioning
confidence: 99%